New Insight Into the Reproductive Biology and Catch of Juveniles of the Lutjanus purpureus in a Portion of the Great Amazon Reef System Off the Northern Brazilian Coast - Freire, Julliany L.; Sarmento, Gabriela C.; Lutz, Ítalo; Bentes, Bianca; Isaac, Victoria J. (Frontiers in Marine Science, 2022)
The Southern red snapper, Lutjanus purpureus, is a valuable economic resource, especially in international market. However, no recent data are available on the reproductive biology of this species in Brazilian waters, in particular, the stock found on the Amazon reef. The present study evaluated the population structure and reproductive biology of L. purpureus, and the volume of the catch of juveniles taken by the local commercial fisheries. A total of 923 specimens were analyzed, of which, 577 were female and 346 male (sex ratio: 0.6:1; p < 0.05). The analysis of the gonadosomatic index (GSI) and the distribution of maturation stages indicated that the males and females are able to reproduce throughout the year, however the reproductive peak occurs simultaneously with the increase in the water discharge of the Amazon River. The spawning females were registered in the study area, indicating that L. purpureus does not perform long distance reproductive migrations, different from the previously proposed. The Fork length at first sexual maturation (FL50) was estimated to be 35.2 cm in the males and 32.1 cm in the females. The high frequency of juveniles (< FL50) captured by the commercial snapper fleet using longlines (33.67% of the total catch) and traps (42.1%) indicates the poor selectivity of the fishing gear used by the snapper fleet, which may contribute to the accelerated depletion of the L. purpureus stock. Although the results of this study show a catch percentage of juveniles >50%, it is still a significant percentage of juveniles that are being caught due to little or no guidance and enforcement of fishing gear to ensure compliance with current legislation. Considering the data presented in this study and the current situation of declining fish stocks of L. purpureus, an assessment is recommended for the inclusion of the species in the IUCN Red List of Threatened Species, which is currently a species categorized as “vulnerable” in the Brazilian Red List.